2017
DOI: 10.1097/nnr.0000000000000230
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Peripheral Artery Disease Symptomatology and Ischemia

Abstract: Background Fewer than half of individuals with peripheral artery disease (PAD) experience classic claudication and the relationships between PAD typical or atypical symptom intensity, location, and description (classic or atypical) with ischemic changes have not previously been reported. Objective The primary purpose of this study was to evaluate the relationship between self-reported PAD symptom intensity and calf tissue ischemia measured using the tissue saturation index (TSI) during treadmill exercise. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In line with these findings, Gardner et al found that the change in TTM correlated significantly with the change in maximal walking time (r=.52, p<.001 and r=.43, p=.006 for home-based and supervised groups, respectively) (26). As TTM commonly appears prior to initial pain experience, these moderate correlations might be explained by the objective and subjective mismatch in pain perception and perseverance following an exercise program (34).…”
Section: Impact Of Exercise On Nirs Parametersmentioning
confidence: 87%
See 1 more Smart Citation
“…In line with these findings, Gardner et al found that the change in TTM correlated significantly with the change in maximal walking time (r=.52, p<.001 and r=.43, p=.006 for home-based and supervised groups, respectively) (26). As TTM commonly appears prior to initial pain experience, these moderate correlations might be explained by the objective and subjective mismatch in pain perception and perseverance following an exercise program (34).…”
Section: Impact Of Exercise On Nirs Parametersmentioning
confidence: 87%
“…and is associated with better ambulatory outcomes (9,32,34). However, only one study found statistically significant results, whereas two others observed trends towards enhanced recovery after submaximal exercise intensity (21) or recovery relative to total exercise time (29).…”
Section: Recovery Concerning Recovery We Noted a Tendency Towards Faster T50 And T100 Following Training Interventions A Faster Reoxygenamentioning
confidence: 99%
“…An explanation for this could be that those patients in the follow-up examinations who were initially diagnosed as LEAD-positive by a specialist after the first screening had already received LEAD-specific medications which reduced or even fully eliminated the symptoms by the time the follow-up examination happened. This again emphasizes the importance of approaching the process of diagnosing LEAD with multiple methods, as diagnosis based solely on ABI can be misleading and leave patients mistakenly categorized as negative despite their symptoms, which can ultimately result in patients unable to receive adequate treatment [17,23,34,35].…”
Section: Reliability Of the Screening Methodsmentioning
confidence: 99%
“…The relationship between symptom intensity and ischemia in PDA is complex and often highly individual. For example, TcPO2 measures recorded during treadmill walking have shown that severe ischemia and pain do not need to occur simultaneously, and that pain can disappear despite persistent significant ischemia, independent of location [43,44]. Nevertheless, Schorr et al reported that roughly 69% of 120 treadmill exercise tests needed to be stopped due to pain [44].…”
Section: Plos Onementioning
confidence: 99%